Library Instruction for Freshman English: A Multi-Year Assessment of Student Learning - Gardner Archambault, Susan (Evidence Based Library and Information Practice, 2011)
Objective – The objective of this study was twofold: 1) to assess the effectiveness of curriculum changes made from the 2009 freshman English library instruction curriculum to the 2010 curriculum at Loyola Marymount University (LMU); and 2) to evaluate the effectiveness of library instruction delivered via a “blended” combination of face-to-face and online instruction versus online instruction alone. Methods – An experimental design compared random samples of student scores from 2009 and 2010 worksheets to determine the effects of a new curriculum on student learning. A second experiment examined the effect of delivery method on student learning by comparing scores from a group of students receiving only online instruction against a group receiving blended instruction. Results – The first component of the study, which compared scores between 2009 and 2010 to examine the effects of the curriculum revisions, had mixed results. Students scored a significantly higher mean in 2010 on completing and correctly listing book citation components than in 2009, but a significantly lower mean on constructing a research question. There was a significant difference in the distribution of scores for understanding differences between information found on the Internet versus through the Library that was better in 2010 than 2009, but worse for narrowing a broad research topic. For the study that examined computer aided instruction, the group of students receiving only computer-assisted instruction did significantly better overall than the group receiving blended instruction. When separate tests were run for each skill, two particular skills, generating keywords and completing book citation and location elements, resulted in a significantly higher mean. Conclusions – The comparison of scores between 2009 and 2010 were mixed, but the evaluation process helped us identify continued problems in the teaching materials to address in the next cycle of revisions. The second part of the study supports the idea that computer-assisted instruction is equally or more effective than blended instruction.